The comparison of the mRNA expressions of TGFβ1, bFGF, IGF-1, NGF, and matrix metalloprotease III genes in cervical and lumbar degenerated disc tissues. (Annals of Medical Research, 2021)
None
Keywords: Degenerated Nucleus Pulposus; mRNA Expression; Cervical; Lumbar.